Papillary Thyroid Cancer and Coexisting Autoimmune Thyroiditis - Veit, Franziska; Graf, Dieter; Momberger, Saskia; Helmich-Kapp, Brigitte; Ruschenburg, Ilka; Peters, Anja; Kussmann, Jochen; Saeger, Wolfgang; Schmidt, Kurt Werner; Toetsch, Martin; Nestler, Kai; Mann, Klaus (Hormone and Metabolic Research, 2017)
Histological findings often display an association between papillary thyroid carcinomas (PTC) and autoimmune thyroiditis (AIT) and so differ significantly from follicular thyroid carcinomas (FTC). The aim of this interdisciplinary, retrospective study was to evaluate the association of AIT in patients with PTC and FTC and a control group of benign nodular goiters. One hundred thyroidectomies with histologically confirmed differentiated thyroid carcinomas, 67 with PTC and 33 with FTC, were submitted for examination. The two control groups consisted of 60 patients with euthyroid nodular goiter, displaying no signs for malignancy (no surgery) and 100 patients (second control group) with surgery of a benign nodular goiter. Controls were collected to obtain data about the incidence of significantly increased TPOAbs in the first group and of lymphocytic infiltrates (LI) in the second group. High TPOAbs were found in 35% (23/67) of patients with PTC. LI were detected by histology in 48% (32/67) of PTC. Ten patients (10/32) of this group showed the clinical and histological manifestation of a classic AIT with diffuse dense LI as well as diffuse hypoechogeneity in ultrasonography. In 7/32 cases, the histological report described focal dense LI (fAIT) and in 15/32 cases scant scattered LI. AIT and fAIT, together 25% of all PTC (17/67), showed germinal centers and can therefore be characterized as chronic autoimmune thyroiditis. In this group, high TPOAb could be detected in 94% (16/17). Scan scattered LI without germinal centers (15/32) do not represent a fAIT, although TPOAb are high in 47% (7/15). The younger age group (<45 years) showed significantly more often high TPOAbs (p<0.023) in comparison with the age-group older than 60 years. In contrast to PTC, only 4/33 (12%) patients with FTC had high TPOAb levels. We conclude that in contrast to benign euthyroid goiters and to FTC, different degrees of LI are often associated with high TPOAb levels and seem to be significantly increased in PTC, particularly prominent in younger age. There is a high coincidence between LI and high TPOAb levels. In the presence of hypoechoic thyroid nodule, signs of thyroid autoimmunity such as the presence of high TPOAbs, lymphocytic infiltration in cytology, and/or characteristic ultrasonic features, are arguments that might favor the decision for surgery if a cytologically indeterminate thyroid nodule is found and focal autonomy is excluded by szintiscan.
Keywords: PTC and AIT; focal AIT; lymphocytic infiltration; papillary thyroid cancer